An examination of MCE filter morphology and implications on preparation and analysis of air samples for asbestos. Issue 9 (2nd September 2017) - Getman, Myron; Webber, James; Bowser, Samuel
ABSTRACT: Morphological imperfections of mixed-cellulose ester filters and their possible influence on sample preparation and analysis of asbestos were examined. Filters were identified with large regions of non-porous "dead zones" which could negatively affect fiber deposition and, therefore, fiber recovery and analysis by Transmission Electron Microscopy (TEM). As these imperfections are effectively erased during the preparation of the sample, they may not be readily observed by TEM. Un-collapsed filters as well as those collapsed using dimethylformamide (DMF) and two acetone techniques were examined. In order to minimize negative sampling and analytical bias, it is suggested that MCE samples be collapsed utilizing a 35% DMF solution, etched with a correctly calibrated low-temperature etcher, carbon coated using a rotating and tilted stage, and analyzed with a strong analyst-independent grid square opening randomization scheme.